IMPLEMENTATION OF SUPPLY CHAIN MANAGEMENT FOR SUSTAINABILITY IN ISLAMIC HIGHER EDUCATION INSTITUTIONS - Azizah, Nur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Supply chain management (SCM) is an integration of material procurement planning activities that can influence the sustainability of an institution. This research discusses the implementation of supply chain management (SCM) as a strategy to achieve sustainability in Islamic higher education institutions. By focusing on the products or results produced by the university. This research uses a qualitative case study type method. Data collection techniques are carried out circularly using three approaches, namely; l) participant observation; 2) in-depth interviews; and 3) documentation. The results of this research show that the implementation of supply chain management at Nurul Jadid University is focused on the preparation of the product itself or output (graduates) that will be marketed to the community in the form of students and research